Suswani Mata Temple - Temples of India Project Team (Jio Institute, 2024)
View of the Suswani Mata Temple from the back side, consisting of the newly added walls surrounding it along with the trees that are considered sacred by devotees. The original shikhara can be seen of the temple. Kera tree to the south side of the temple, latina nagara shikhara.